REFUGIA PLANTS AS NATURAL ENEMY MICROHABITAT FOR PEST CONTROL ON MANGO (Mangifera indica L.) FARMER GROUP SUKODADI PASURUAN - Wiwin Windriyanti; Noni Rahmadhini; Dita Megasari; Ramadhani Mahendra Kusuma; Yudi Nur Supriadi (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The utilization of refuge plants as microhabitats for natural enemies has been explored as a sustainable approach to pest control in mango cultivation. This community service project aimed to assess the feasibility and effectiveness of implementing refuge plants for pest management in the Sukodadi Farmer Group, Pasuruan Regency. The background highlighted the challenges faced by mango farmers, including pest infestations and the negative impacts of chemical pesticides on the environment and human health. The methodology involved socialization and demonstrating the use of refugees around mango fields. The participation and enthusiasm of the farmers were remarkable, as they gained valuable knowledge and confidence in implementing environmentally friendly pest and disease management practices. The farmers observed a reduction in pest populations and improved crop health. The active involvement of the farmers in the project increased their understanding of sustainable pest management practices and enhanced their confidence in implementing these methods. This community service project contributes to the knowledge and implementation of integrated pest management strategies in mango cultivation. The findings emphasize the significance of utilizing refuge plants as microhabitats for natural enemies to enhance pest control and promote the sustainability of mango production. The outcomes serve as a valuable resource for farmers, extension workers, and policymakers involved in agricultural practices in Sukodadi and similar regions